Optimizing Software Development and Quality in the Finnish Software Industry: Agile Practices and Quality Management - Veronika, Shalini Rathnayake Mudiyanselage (My University, 2025)
ABSTRACT: The Finnish software industry is a dynamic and technologically advanced sector, comprising a diverse mix of startups and multinational firms engaged in software development, consulting, and IT services. Agile methodologies have become foundational to this ecosystem, widely adopted to enhance development speed, adaptability, and customer satisfaction. However, optimizing Agile implementation to consistently improve software quality remains a central challenge for practitioners and researchers alike. This thesis investigates the impact of Agile practices on software quality and customer satis- faction within the Finnish software sector. A conceptual framework was developed around five core dimensions: Agile testing practices ,adherence to Agile principles, iteration frequency, test automation maturity, and customer feedback integration. Employing a quantitative, cross- sectional research design, the study utilized a structured survey instrument targeting software developers, QA engineers, project managers, and Agile coaches. A total of 200 valid responses were collected and statistically analyzed using Pearson correlation and multiple linear regres- sion to evaluate the relationships between Agile practices and key software outcomes. The thesis is organized into five chapters. Chapter one establishes the research background and objectives. Chapter two reviews key theoretical foundations in Agile methodology, soft- ware quality engineering, and customer-centric development. Chapter three details the meth- odological approach, including sampling, instrument design, and validation techniques. Chap- ter four presents the empirical results, while chapter five discusses conclusions, practical im- plications, limitations, and future research directions. Findings demonstrate that Agile testing practices and high iteration frequency exert the strongest positive influence on software quality and customer satisfaction. Automation prac- tices and structured feedback loops also contribute meaningfully, though their impact may vary across organizational contexts. The reliability of the instrument, tested through Cronbach’s alpha (α = 0.700), supports the internal consistency of key measurement scales, while statistical diagnostics confirm the robustness of the regression model. Despite limitations such as potential self-reporting bias and the regional focus, this study pro- vides actionable insights for software teams seeking to align Agile practices with quality assur- ance goals. It highlights the strategic importance of continuous integration, iterative develop- ment, and collaborative feedback mechanisms in optimizing software performance and stake- holder satisfaction. KEYWORDS: Agile practices, software quality, Agile testing, customer satisfaction, continuous integration, test automation, TDD, BDD, regression analysis, quantitative research
Keywords: agile methods; software development; software engineering; quality management; customer satisfaction; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management